Elucidating the Effect of Learning Ability on Employees’ Potential : A Study of IT Sector in India - Verma, Anju; Singh, Pradeep (Prabandhan: Indian Journal of Management, 2020)
It is seen that information technology (IT), being a knowledge-based sector, always faces a question of employee retention. Organizations have tried to get the answer of this question by exploring the ways to improve employees’ satisfaction with their organizations. Proper exploitation of employees’ potential may be felt as an answer to this question. Employees’ potential is enhanced by improving learning ability. Thus, this study was designed with an aim to explore the effect of learning ability on employees’ potential. An exhaustive literature review was done in order to confirm the variables of the study as well as to get the clear directions for the current research. A total of 455 employees of various IT sectors were investigated during the study. The survey was conducted during May 2016 and September 2017. Primary data were collected using a well-structured questionnaire. Employees’ potential was explained through four dimensions, namely technical competencies, managerial competencies, interpersonal competencies, and personal competencies. The effect of learning ability on employees’ potential was expounded by applying regression models. The results concluded that learning ability came out as a strong predictor of personal competencies and moderate predictor for managerial competencies. Technical competencies were not found to be significantly related to learning ability. Furthermore, a vice versa effect of personal competencies on learning ability was also extracted. In addition, managerial competencies, interpersonal competencies, and personal competencies exhibited a strong relationship.